Characteristics of newborns with necrotizing enterocolitis in a third-level university hospital in Colombia (Colombia Medica, 2011)
Introduction: Necrotizing enterocolitis (NEC) is, over all newborn surgical afflictions, the most deathly, representing the main GI problem in neonatal intensive care units (NICU) and a medical/surgical emergency in which early diagnosis and opportune treatment may diminish surgical needs and mortality. Objective: To describe the features of patients with NEC attended at a third-level hospital NICU in the city of Cali in 2006.Method and materials: We conducted a pilot descriptive retrospective study that included 32 clinical records of newborns in the NICU (named CIRENA) from the Hospital Universitario del Valle (HUV) with NEC diagnosis. Finally, we made a descriptive analysis of the data by using the Epi-Info statistics program. Results: In 2006, 1555 newborns were admitted to HUV-CIRENA and 32 (2%) of them were diagnosed with NEC, a percentage that is similar to that of other countries; half of which weighed less than 1500 grams and only three pregnant women had adequate prenatal care, 17(53.1%) of these newborns were female and 15(46.9%) were male.       Conclusions: Although the majority of NEC cases occurs in premature and/or very low weight children, it is outstanding the number of full-term newborns, either on gestational age and weight, that developed early NEC. There is a visible relationship among low birth weight, prematurity, and the development of NEC, especially in the higher degrees of the disease, where the tendency is the presentation of late NEC.